PERANCANGAN SISTEM PEMELIHARAAN MOBIL BERBASIS PROXIMITY MENGGUNAKAN METODE LOCATION BASED SERVICE - Tani, Stenley Laorence (TEMATIKA, Journal of Informatics and Information Systems, 2020)
Vehicles often experience problem, especially engine problems. One of the problems was caused by the vehicle owner forgetting to do periodic service or maintenance to his vehicle. So, if the Car engine is delayed in service, the performance of the engine will be reduced and not optimal in its use. The workshop only reminds us of the service through receipt or sticker it becomes a problem when the sticker is missing and the Customer is not careful to save it. To solve this problem, the authors use the location based services method to get vehicle mileage and vehicle travel time to get regular service data. location based services are location-based services or general terms that are often used to describe the technology used to find the location of the device the user is using. This service uses Google's global positioning service (GPS) technology and cell-based location. Simply put, with the LBS service, aside from being a location indicator, the Google Maps application can also be used as a tool to measure the vehicle's time and distance. At the development stage the researcher uses the waterfall method of research duration from the analysis, design, coding, testing, and implementation stages for 10 months. The results of the study based on 10 respondents indicate a system proposed by the author that can provide information or information about the owner of the car related to the next service.